The facial profile in the context of facial aesthetics - Heppt, Werner; Vent, Julia (Facial plastic surgery, 2015)
Beauty has been an intriguing issue since the evolving of a culture in mankind. Even the Neanderthals are believed to have applied makeover to enhance facial structures and thus underline beauty. The determinants of beauty and aesthetics have been defined by artists and scientists alike. This article will give an overview of the evolvement of a beauty concept and the significance of the facial profile. It aims at sharpening the senses of the facial plastic surgeon for analyzing the patient's face, consulting the patient on feasible options, planning, and conducting surgery in the most individualized way.